Inquiry-Based Mathematics Teaching: The Case of Célia - Menezes, Luís (2015)
Over the last decades many perspectives on mathematics teaching have emerged in opposition to the common vision and practice of knowledge transmission. Proposals for the transformation of the school mathematics curriculum are anchored to new approaches to the possibility for students to learn mathematics meaningfully. The ideas of an inquiry-based approach to teaching, in opposition to the transmission model, echo Dewey’s perspectives, where students’ activity is central to the development of the learning process.